Similar cardiac remodelling after transcatheter atrial septal defect closure in children and young adults. Issue 7 (9th December 2005) - Santoro, G; Pascotto, M; Caputo, S; Cerrato, F; Cappelli Bigazzi, M; Palladino, M T; Iacono, C; Carrozza, M; Russo, M G; Calabrò, R
Abstract : Objective: To study the cardiac geometric changes after transcatheter closure of large atrial septal defects (ASDs) according to patient age at the time of the procedure. Design: Prospective echocardiographic follow-up study. Setting: Tertiary referral centre. Patients and intervention: 25 asymptomatic patients younger than 16 years (median 8 years; group 1) and 21 asymptomatic adults (median 38 years; group 2) underwent percutaneous closure of large ASD with the Amplatzer septal occluder device (mean 25 (SD 7) mm). Main outcome measures: Cardiac remodelling was assessed by M mode and two dimensional echocardiography one and six months after ASD closure. Results: By six months, right atrial volume decreased from 31 (15) to 19 (5) ml/m 2 (p < 0.001) and right ventricular (RV) transverse diameter decreased from 29.8 (8.6) to 23.2 (5.6) mm/m 2 (p < 0.001). Conversely, left atrial volume did not change significantly (from 18 (6) to 20 (6) ml/m 2, NS) and left ventricular (LV) transverse diameter increased from 27.8 (6.4) to 31.8 (7.3) mm/m 2 (p < 0.05). Ventricular remodelling resulted in an RV:LV diameter ratio decrease from 1.1 (0.2) to 0.7 (0.1) (p < 0.001). The magnitude and time course of cardiac remodelling did not differ significantly between the age groups. Indeed, right atrial volume decreased by 33 (26)% versus 37 (23)%, RV diameter decreased by 26 (10)% versus 20 (13)%, LV diameter increased by 17 (15)% versus 15 (10)%, and RV:LV diameter ratio decreased by 36 (8)% versus 27 (15)% in groups 1 and 2, respectively. Conclusions: Cardiac remodelling after percutaneous ASD closure seems to be independent of the patient's age at the time of the procedure up to early adulthood. Thus, postponing ASD closure for a few years may be a reasonable option for potentially suitable asymptomatic children.